2017
DOI: 10.1002/chem.201705016
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐ and Supporting‐Electrolyte‐Free Electrosynthesis of Benzothiazoles and Thiazolopyridines in Continuous Flow

Abstract: A catalyst- and supporting electrolyte-free method for electrochemical dehydrogenative C-S bond formation in continuous flow has been developed. A broad range of N-arylthioamides have been converted to the corresponding benzothiazoles in good to excellent yields and with high current efficiencies. This transformation is achieved using only electricity and laboratory grade solvent, avoiding degassing or the use of inert atmosphere. This work highlights three advantages of electrochemistry in flow, which is (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 68 publications
(69 reference statements)
0
70
0
Order By: Relevance
“…[10] These electrosynthetic methods require no transition-metal catalysts and oxidizing reagents but do need supporting electrolytes such as tetraalkylammonium salts to increase the conductivity of the organic reaction mixture. [13] Despite the extensive studies on the dehydrogenative CÀSc oupling for the synthesis of benzothiazoles,a nalogous reactions for the synthesis of benzofused six-membered heterocycles remain an unsolved challenge,probably because thioamides,especially alkylthioamides,are prone to oxidative desulfurization. [11,12] However,a pplications of this enabling technology in the discovery of new reactions remain rare.I n collaborative effort with the group of Wirth, we have achieved the continuous-flow electrochemical synthesis of benzothiazoles under catalyst and supporting electrolyte free conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] These electrosynthetic methods require no transition-metal catalysts and oxidizing reagents but do need supporting electrolytes such as tetraalkylammonium salts to increase the conductivity of the organic reaction mixture. [13] Despite the extensive studies on the dehydrogenative CÀSc oupling for the synthesis of benzothiazoles,a nalogous reactions for the synthesis of benzofused six-membered heterocycles remain an unsolved challenge,probably because thioamides,especially alkylthioamides,are prone to oxidative desulfurization. [11,12] However,a pplications of this enabling technology in the discovery of new reactions remain rare.I n collaborative effort with the group of Wirth, we have achieved the continuous-flow electrochemical synthesis of benzothiazoles under catalyst and supporting electrolyte free conditions.…”
mentioning
confidence: 99%
“…[11,12] However,a pplications of this enabling technology in the discovery of new reactions remain rare.I n collaborative effort with the group of Wirth, we have achieved the continuous-flow electrochemical synthesis of benzothiazoles under catalyst and supporting electrolyte free conditions. [13] Despite the extensive studies on the dehydrogenative CÀSc oupling for the synthesis of benzothiazoles,a nalogous reactions for the synthesis of benzofused six-membered heterocycles remain an unsolved challenge,probably because thioamides,especially alkylthioamides,are prone to oxidative desulfurization. [14] Herein we report the synthesis of 1,4benzoxathiins and 1,4-benzothiazines using aflow electrolysis cell by intramolecular dehydrogenative CÀSc ross-coupling (Scheme 1B).…”
mentioning
confidence: 99%
“…In this method, an easy scale-up of the reaction without the need for a larger reactor largely improved the reported methods for the formation of benzothiazoles. Folgueiras et al [71] have reported that the catalyst-free and supporting electrolyte-free electrochemical synthesis of benzothiazoles has good to excellent yields and with high current efficiencies from arylthioamides using a flow electrochemical reactor (Scheme 30). In this method, an easy scale-up of the reaction without the need for a larger reactor largely improved the reported methods for the formation of benzothiazoles.…”
Section: Scheme 29 Cyclization Of Thioanilidesmentioning
confidence: 99%
“…Using an electrochemical microreactor, Wirth et al . developed a flow protocol for the synthesis of diaryliodonium salts.…”
Section: Electrochemical Generation Of Hypervalent Iodine Reagentsmentioning
confidence: 99%
“…Using an electrochemical microreactor, [49][50][51][52][53] Wirth et al [54] developedaflow protocol for the synthesis of diaryliodonium salts. The microreactor consists of two platinum electrodes separated by at hin (250 mm) fluorinated ethylene propylene (FEP) foil containing ac hannel of 23 mLv olume( Figure 1).…”
Section: Electrochemical Synthesis Of Diaryliodonium Saltsmentioning
confidence: 99%